The effects of restricting enzyme supplementation in rye-based diets for broilers - Santos, C.I. (2013)
The purpose of the current study was to restrict enzyme addition in order to evaluate if supplementation throughout the broiler production cycle is required. Here we analyze the possibility of circumscribing xylanase supplementation in rye-based diets to the earliest periods of the life of the broiler. In the current experiment, 1-day-old chicks were divided into 5 treatments and fed a rye-based diet supplemented with a commercial enzyme mixture containing a microbial xylanase. The five treatments consisted of birds fed a nonsupplemented diet and birds fed diets supplemented with the exogenous enzyme for the entire period of the experiment (28 days), the first 21 days, the first 14 days or the first 7 days of the trial. The data revealed that broilers fed diets supplemented with enzymes during 28 days had similar (P>0.05) growth performance, gastrointestinal enzyme activity and relative organ sizes to broilers fed supplemented diets only in the first 21 days of the experimental period. These results suggest that the action of exogenous enzymes, when used to supplement rye-based diets for broilers, may be restricted to the first 21 days of the broiler’s production cycle without compromising animal performance